Ketogenic diet does not promote triple-negative and luminal mammary tumor growth and metastasis in experimental mice - Grube, Meret; Dimmler, Arno; Schmaus, Anja; Saup, Rafael; Wagner, Tabea; Garvalov, Boyan K.; Sleeman, Jonathan P.; Thiele, Wilko (Clinical & experimental metastasis, 2023)
Ketogenic diets (KDs) can improve the well-being and quality of life of breast cancer patients. However, data on the effects of KDs on mammary tumors are inconclusive, and the influence of KDs on metastasis in general remains to be investigated. We therefore assessed the impact of a KD on growth and metastasis of triple negative murine 4T1 mammary tumors, and on the progression of luminal breast tumors in an autochthonous MMTV-PyMT mouse model. We found that KD did not influence the metastasis of 4T1 and MMTV-PyMT mammary tumors, but impaired 4T1 tumor cell proliferation in vivo, and also temporarily reduced 4T1 primary tumor growth. Notably, the ketogenic ratio (the mass of dietary fat in relation to the mass of dietary carbohydrates and protein) that is needed to induce robust ketosis was twice as high in mice as compared to humans. Surprisingly, only female but not male mice responded to KD with a sustained increase in blood β-hydroxybutyrate levels. Together, our data show that ketosis does not foster primary tumor growth and metastasis, suggesting that KDs can be safely applied in the context of luminal breast cancer, and may even be advantageous for patients with triple negative tumors. Furthermore, our data indicate that when performing experiments with KDs in mice, the ketogenic ratio needed to induce ketosis must be verified, and the sex of the mice should also be taken into account.
Online veröffentlicht: 9. Dezember 2023
Gesehen am 06.06.2024